A re(a)presentação da velhice e corpo na universidade - Pereira, Mário César da Silva (2015)
Anthropology through man's recognition about yourself enables a connection point between the human, social and biological sciences. In this context, deals with the question of how society deals with the body and its transformations in the symbolic level, physical, individual and collective. The age and the recognition of this phenomenon goes beyond the frontiers of biological, because, it is argued from personal, cultural, and social references. The global population aging is an irreversible reality. Education is a transforming agent of society to develop values such as critical awareness, consistency and ethics. Investments in this sector in Brazil are still below their needs. Physical therapy occupies in the field of health sciences the role of curative, preventive and palliative functional disabilities This study aims to analyze the relationship between age and the body played by teacher and students in the discipline of course Gerontology Physiotherapy a public higher education institution in the state of Paraná. The sample consisted of 11 subjects, one teacher and 10 students. Considerations about aging prepared by the teacher are based heavily by the biological and technical activities context, however already see an attempt to overcome this framework, therefore, the analysis of the questionnaires shows that old age in society for teachers has a direct relationship with the increase the world's elderly population and believes that much of society is not prepared for intergenerational families. This fact, there has been in the old valuation duality that to have good quality of life, health and provision is taken as an example of good old age, however, when sick or need care, are excluded by a large number of people. Despite this contradiction contribute to the development of society and aging is inevitable, but the physical body condition is important to define old age as healthy, even with the presence of morbidity. To this end, the adoption of preventive programs is essential. Students understand old age as a result of demographic transition in the age structure and detach the perception of association with disease to consider it as a life stage. Therefore, the elderly represent a subject category that influences and is influenced by economic groups, financial and political. Body and old age suffer inevitable transformations, namely frailty, functional decline and appearance are indicators of such a condition, so healthy bodies are benchmarks of a healthy old age and prevention programs are essential